Investigations of internal friction and constants of elasticity of solids by the acoustic resonance method - S. PILECKI; P. KOPANIA (Archives of Acoustics)
Results of measurements of the internal friction, Poisson's constant and Young's modulus for various metals: copper, aluminium, copper without oxygen, brass, aluminium and silicon bronzes, in different states of deformation and heat treatment, were presented. Discovery of the formerly unknown anomaly of internal friction in a plastically deformed silicon bronze BK31, occurring in the temperature range 400-500K, was discussed. A number of effects that accompany this phenomenon were described, together with attempts of explanation of its physical mechanism.